2003
DOI: 10.3759/tropics.13.89
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide variation in the GapC region of four species of Shorea and their putative hybrids

Abstract: Very little is known about the levels and patterns of DNA polymorphism in populations of tropical trees. In this study, we investigated population genetic structure of the four following Shorea species: Shorea acuminata, S. curtisii, S. leprosula and S. parvifolia from peninsular Malaysia using DNA sequences of Glyceraldehyde-3-phosphate dehydrogenase nuclear gene (GapC). The average nucleotide diversities of the investigated species for silent sites ( sil = 0.0027) were lower than those reported for herbaceou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Hybridization among Shorea species has been reported in previous studies (ASHTON, 1982;HARADA et al, 1994;ISHIYAMA et al, 2003;ISHIYAMA et al, 2008). Based on sequences of the nuclear GapC and PgiC genes ISHIYAMA et al (2003ISHIYAMA et al ( , 2008 found similar or identical haplotypes and proposed the occurence of inter-specific hybridization between four Shorea species: S. acuminata, S. curtisii, S. leprosula and S. parvifolia.…”
Section: Comparison Between Chloroplast Dna and Scar Markersmentioning
confidence: 98%
See 2 more Smart Citations
“…Hybridization among Shorea species has been reported in previous studies (ASHTON, 1982;HARADA et al, 1994;ISHIYAMA et al, 2003;ISHIYAMA et al, 2008). Based on sequences of the nuclear GapC and PgiC genes ISHIYAMA et al (2003ISHIYAMA et al ( , 2008 found similar or identical haplotypes and proposed the occurence of inter-specific hybridization between four Shorea species: S. acuminata, S. curtisii, S. leprosula and S. parvifolia.…”
Section: Comparison Between Chloroplast Dna and Scar Markersmentioning
confidence: 98%
“…Based on sequences of the nuclear GapC and PgiC genes ISHIYAMA et al (2003ISHIYAMA et al ( , 2008 found similar or identical haplotypes and proposed the occurence of inter-specific hybridization between four Shorea species: S. acuminata, S. curtisii, S. leprosula and S. parvifolia. In contrary, CAO et al (2006) found strong frequency differences in AFLP bands between species and a clear separation of S. leprosula and S. parvifolia based on the AFLP markers.…”
Section: Comparison Between Chloroplast Dna and Scar Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these studies are reported at this workshop by researchers at Kyushu University (Dayananda et al, 2003;Ishiyama et al, 2003;Sirikantamaras et al, 2003).…”
mentioning
confidence: 94%
“…However, sequencing of the nuclear PgiC (phosphoglucose isomerase) gene in Shorea revealed that species belonging to each of the three timber groups balau, yellow meranti, and red meranti formed one specific (monophyletic) clade within Shorea (Kamiya et al 2005). Additional information on variation in nuclear gene markers is available for genus Shorea for the GapC (glyceraldehyde-3-phosphate dehydrogenase) region (Ishiyama et al 2004) and the ITS regions (K.S. Yulita & R.J. Bayer, unpublished; see Chapter 9 for a general explanation of the ITS regions).…”
mentioning
confidence: 99%